Europium(iii)-containing nanohydrogels for cellular imaging and drug delivery applications. Issue 29 (16th June 2021) - Wang, Yicheng; Wang, Yuxin; Hu, Yaqin; Yang, Wen Jing; Wang, Lianhui
Abstract : By employing the excellent luminescence of Eu(iii ) complexes and the versatility of nanohydrogels, Eu(iii )-containing nanohydrogels were prepared as a potential theranostic nanoplatform for cancer therapy. Abstract : The design of europium(iii )-based (Eu(iii )-based) nanomaterials with good water dispersity and high fluorescence is of great importance for their bioapplication. In this work, Eu(iii )-containing nanohydrogels were fabricated by a facile reflux-precipitation polymerization and their potential as theranostic nanomaterials were explored. The resultant PAAEu nanohydrogels (NGs) exhibited excellent monodispersity, high aqueous stability and strong fluorescence intensity. They could be internalized by cancer cells and showed high fluorescence signals after 5 hours of incubation. The in vitro cell assays confirmed the good cytocompatibility of PAAEu NGs with a cell viability of above 90% after 12 hours. After loading with the anticancer drug doxorubicin (Dox), Dox@PAAEu NGs induced cell apoptosis and necrosis and exhibited high cytotoxicity towards cancer cells. The prepared Eu(iii )-containing nanohydrogels could be employed as theranostic nanomaterials for bioimaging and drug delivery applications.